A Many‐Body Perturbation Theory Approach to Energy Band Alignment at the Crystalline Tetracene–Silicon Interface. Issue 11 (19th August 2022) - Klymenko, Mykhailo V.; Tan, Liang Z.; Russo, Salvy P.; Cole, Jared H.
Abstract: Hybrid inorganic–organic semiconductor (HIOS) interfaces are of interest for new photovoltaic devices operating above the Shockley–Queisser limit. Predicting energy band alignment at the interfaces is crucial for their design, but represents a challenging problem due to the large scales of the system, the energy precision required and a wide range of physical phenomena that occur at the interface. To tackle this problem, many‐body perturbation theory in the non‐self‐consistent GW approximation, orbital relaxation corrections for organic semiconductors, and line‐up potential method for inorganic semiconductors which allows for tractable and accurate computing of energy band alignment in crystalline van‐der‐Waals hybrid inorganic–organic semiconductor interfaces are used. In this work, crystalline tetracene physisorbed on the clean hydrogen‐passivated 1 × 2 reconstructed (100) silicon surface is studied. Using this computational approach, it is found that the energy band alignment is determined by an interplay of the mutual dynamic dielectric screening of two materials and the formation of a dipole layer due to a weak hybridization of atomic/molecular orbitals at the interface. The significant role of the exchange‐correlation effects in predicting band offsets for the hybrid inorganic–organic semiconductor interfaces is also emphasized. Abstract : Interfaces between organic and inorganic semiconductors are of interest for modern photovoltaics and optoelectronics. Predicting energy band alignment at such interfaces represents a challenging problem due to the large scales of the system and a wide range of physical phenomena that occur at the interface. In this work, the key contributions to the energy band alignment are quantitatively estimated.